Sandcastle Resort’s Corporate Governance and Business Performance Issues During the COVID-19 Pandemic - Kishana, K.; Azhar, Zubir (2022)
Sandcastle Resort is one of Malaysia’s ideal lifestyle and staycation attraction centres. With four resorts spread around the country, Sandcastle Resort renders tourism and hospitality services that guarantee more than just a place to stay. Each resort provides a sociable environment and leisure experience that goes beyond the expectations of guests. However, the COVID-19 pandemic caused the Malaysian government to institute a nationwide lockdown beginning in March 2020 to control the spread of the virus. As a result, Sandcastle Resort’s business performance was severely impacted because it incurred operating costs but generated no revenue. Hence, the top management considered some questionable earnings management techniques to mask the poor financial performance. The pandemic also cast a light on the resort’s corporate governance weaknesses such as the independence of its internal auditor and its internal controls. Additionally, the pandemic underscored the need to utilize technology to improve operational efficiency and attract customers for the resort to survive and flourish.